Produksi Eco-Enzyme dengan Pemanfaatan Limbah Rumah Tangga Untuk Larutan Pembersih Serbaguna dan Pupuk Tanaman - Firja, Meyronita; Fauzy, Arif; Ratnasari, Dini; Monika, Febiyola; Nurcahyono, Joko; Meybira, Kesya; Sari, Lilik Nur Indah; Safitri, Rosalinda Nur; Sari, Suci Septika; Anjani, Tania Fetri (Abdimas Indonesian Journal, 2024)
Eco-enzyme is a versatile solution produced from the fermentation of household organic waste, such as fruit and vegetable scraps, with sugar and water. This product offers various benefits, including use as a multi-purpose cleaner, plant fertilizer, and odor eliminator. This article provides a detailed discussion on the production process of eco-enzyme, from material preparation to fermentation and filtration stages. Using a ratio of 3:1:10 between organic waste, sugar, and water, eco-enzyme can be easily produced at home. In addition to reducing organic waste, which contributes to environmental issues, eco-enzyme offers a more eco-friendly alternative compared to chemical cleaners and fertilizers. The article also offers practical suggestions for enhancing the effectiveness of eco-enzyme production and usage, as well as the importance of education and collaboration in organic waste management. By utilizing eco-enzyme, we can contribute to environmental preservation and create a more sustainable future.